Mapping the relationships among sleep, motor balance, and cognition in older adults: a systematic scoping review - Shin, Yun Chan; Shah, Shrinath; Sejpal, Hailey Manoj; Wang, Hongwu (Frontiers in Human Neuroscience, 2025)
IntroductionSleep, motor balance, and cognitive function are critical for maintaining functional independence in older adults, yet their interrelationships remain poorly understood. This systematic scoping review maps the evidence on pairwise and triadic relationships among these domains in older adults.MethodsFollowing the JBI Manual for scoping reviews, we searched PubMed, Web of Science, CINAHL, and Embase for studies (January 1, 2004–March 1, 2024) involving older adults (≥60 years) that examined sleep, motor balance, and cognition. Covidence facilitated a two-phase screening, selecting studies assessing all three domains. Data on study design, participant characteristics, and outcome measures were extracted, with evidence levels assessed using NHMRC guidelines.ResultsFrom 1,367 studies, 33 (7 experimental, 26 observational) involving 67,237 older adults were included. Sleep quality showed weak to moderate positive associations with motor balance (e.g., r = 0.1–0.3) and cognition, while motor balance confidence was positively linked to cognition. Only one study explored triadic interactions, revealing a significant gap. Effect sizes suggest limited clinical significance in some findings.ConclusionPairwise relationships among sleep, motor balance, and cognition are evident but weak. Longitudinal, multimodal intervention studies are needed to explore triadic interactions and inform integrated interventions.